1966
DOI: 10.2466/pms.1966.22.3.763
|View full text |Cite
|
Sign up to set email alerts
|

Pain Reactivity and Kinesthetic Aftereffect

Abstract: The previously reported relationship between reaction to suprathreshold pain and kinesthetic aftereffect was substantiated, the pain being induced by exposure of the hand to cold air. Three groups ( nt = 9) constructed to represent three levels of reported pain reactivity differed in extent of kinesthetic aftereffect as measured by displacement of post-inspection judgments from control PSE. Those of highest reported pain reactivity showed the least displacement. The groups did not differ in recovery from after… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
18
0

Year Published

1974
1974
1977
1977

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 9 publications
3
18
0
Order By: Relevance
“…Petrie (1967) and Silverman (1968) A number of studies found support for the validity of the one-hand variant of the KAE procedure to which this paper is restricted. Petrie, Collins, and Solomon (1958), Poser (1960), Ryan and Foster (1967), and Sweeney (1966) each reported findings consistent with the view that reducers show greater tolerance for the high intensity stimulus of pain than augmenters. Under low levels of stimulus intensity, such as sensory deprivation, reducers are less tolerant (Petrie et a1., 1958) and physically more active (Sales, 1971--Exp.…”
Section: Introductionsupporting
confidence: 62%
See 1 more Smart Citation
“…Petrie (1967) and Silverman (1968) A number of studies found support for the validity of the one-hand variant of the KAE procedure to which this paper is restricted. Petrie, Collins, and Solomon (1958), Poser (1960), Ryan and Foster (1967), and Sweeney (1966) each reported findings consistent with the view that reducers show greater tolerance for the high intensity stimulus of pain than augmenters. Under low levels of stimulus intensity, such as sensory deprivation, reducers are less tolerant (Petrie et a1., 1958) and physically more active (Sales, 1971--Exp.…”
Section: Introductionsupporting
confidence: 62%
“…Consequently, the KAE score in a later session would represent the difference between two similar scores rather than between a true pre-and post-stimulation score. Poser, 1960;Ryan & Foster, 1967;Sales, 1971;Sales, 1972;Sales & Throop, 1972;Sweeney, 1966) while only 5 were nonsupportive (Becker, 1960;Broadbent, 1961;Brown, 1965;Howarth, 1963;Norcross, Lipman, & Spitz, 1961). This evidence indicates that single-session KAE is valid and therefore possesses true reliability.…”
Section: Multidimensional Scaling Analysis the Guttman-lingoes Smallmentioning
confidence: 73%
“…Collins, and Solomon (1958), Poser (1960), Ryan and Foster (1967) and Sweeney (1966) each reported findings consistent with the view that Reducers show greater pain tolerance than Augmenters.…”
supporting
confidence: 66%
“…At the other extreme, people who judged the standard block as relatively larger after as compared to before stimulation are called Augmenters because they presumably magnify the subjective intensity of incoming stimulation; they are therefore Early validity studies supported this view. For example, under the high intensity stimulation of pain, Reducers showed greater tolerance than Augmenters (Petrie, Co1lins t & Solomon, 1958;Poser, 1960;Sweeney, 1966). However, when the stimulus situation involved the very low intensity stimulation of sensory deprivation, Reducers were found to be less tolerant (Petrie et al t 1958) and physically more active (Sa1es t 1971) than Augmenters.…”
mentioning
confidence: 99%
“…In another variant of the KAE task, the subject simultaneously rubs two stimulus blocks--a larger one with one hand, a smaller with the other (e.g., Spilker & Callaway, 1969).. this paper is delimited to reliability and validity issues which arise when the one-hand procedure is used and does not consider issues arising with employment of the two-hand variant. Solomon, 1958;Poser, 1960;Sweeney, 1966 We contend that first-session KAE scores possess true test reliability because they have demonstrated concurrent and construct validity relationships with personality and cognitive variables. Our view is based on logical and empirical grounds.…”
mentioning
confidence: 99%